Finite difference method accelerated with sparse solvers for structural analysis of the metal-organic complexes. (May 2016) - Guda, A A; Guda, S A; Soldatov, M A; Lomachenko, K A; Bugaev, A L; Lamberti, C; Gawelda, W; Bressler, C; Smolentsev, G; Soldatov, A V; Joly, Y
Abstract: Finite difference method (FDM) implemented in the FDMNES software [Phys. Rev. B, 2001, 63, 125120] was revised. Thorough analysis shows, that the calculated diagonal in the FDM matrix consists of about 96% zero elements. Thus a sparse solver would be more suitable for the problem instead of traditional Gaussian elimination for the diagonal neighbourhood. We have tried several iterative sparse solvers and the direct one MUMPS solver with METIS ordering turned out to be the best. Compared to the Gaussian solver present method is up to 40 times faster and allows XANES simulations for complex systems already on personal computers. We show applicability of the software for metal-organic [Fe(bpy)3 ] 2+ complex both for low spin and high spin states populated after laser excitation.